Effect of Sawdust and Zirconia Addition on the Dielectric Strength of Iraqi Kaolin Composite. (Journal of University of Babylon for Engineering Sciences, 2019)
Iraqi kaolin  is used as a principle part of the study after additives Sawdust in weight ratio (10%) and (2%) Poly Vinyl Alcohol (PVA) as a binding material. (Micro or Nano) Zirconia has been added to the composite in different weight ratio (0%, 5%, 10%, 15%, 20%) for the purpose of improving dielectric strength. Samples are formed in a semi-dry pressing with pressure of about (20 Mpa).The formulation is achieved by using a template of (12 mm) diameter and a time of about (2 min). Then, the prepared samples have been sintered.Firing process was carried out by three temperature degrees ( 800, 900, 1000 ) ºC for mean heating about 5 ºC/min and remained at every temperature degree for one hour.The results showed that the increase in the proportion of (Micro or Nano) Zirconia results in increasing the value of dielectric strength and the best results where achieved by adding Nano Zirconia. The increasing of the Firing temperature also leads to increase the value of the dielectric strength.